Investigation into the dynamics of wheel spray released from a rotating tyre of a simplified vehicle model. Issue 184 (January 2019) - Kabanovs, Anton; Garmory, Andrew; Passmore, Martin; Gaylard, Adrian
Abstract: Accurate prediction of vehicle soiling is an important step towards being able to understand and reduce this problem. Previous work has shown that eddy resolving CFD methods are capable of predicting the soiling pattern on the surface of automotive geometries when a known spray source is used. Here the influence of the wheel, ground and spray boundary conditions on a simulation of rear soiling of a generic SUV are investigated. The inclusion of rotating wheels led to a greater vertical distribution of the soiling pattern whereas the moving ground plane led to increased lateral distribution. The total soiling rate with moving wheels and ground, as well as with the offset between wheel and ground removed, was approximately 50% higher than the experimental conditions. When spray was released from around the rotating wheel it was found that a large majority of the parcels which ended up on the base originated from close to the contact patch, indicating that this is the most important region for the tyre spray model. A model based on a measured distribution of droplet sizes from downstream of the wheel gave good agreement with previous experimental work for the spray topology around the contact patch. Highlights: Addition of moving wheels and ground leads to 50% higher predicted base soiling. Most of base soiling particles originate close to the contact patch of the tyre. More realistic spray near contact patch from range of drop sizes than single size.